Enhancing creative process engagement in university students: the mediating role of trust and empowerment and the moderating effect of proactive personality in humble teacher leadership - Xiyue Zhang; Jingming Chi (BMC Psychology)
Abstract This study examines the interplay between humble teacher leadership and student creative process engagement, grounded in Social Exchange Theory and Self-Determination Theory. Additionally, it analyzes the sequential mediating roles of student trust and psychological empowerment, as well as the moderating effect of proactive personality. Data were collected at three time points from 384 participants across Chinese universities and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with Smart PLS 4.0 software. The findings reveal that humble teacher leadership significantly enhances students’ participation in creative processes. Student trust and psychological empowerment serve as sequential mediators in the relationship between humble leadership and creative engagement. Moreover, the presence of a proactive personality notably strengthens the positive influence of humble teacher leadership on students’ creative process engagement. By exploring the psychological states and individual differences, this research elucidates the mediating mechanisms and boundary conditions between humble teacher leadership and students’ creative engagement, providing theoretical foundations and practical guidelines for implementing humble leadership in educational settings.